2012
DOI: 10.1007/s10578-012-0310-5
|View full text |Cite
|
Sign up to set email alerts
|

Dismissing Children’s Perceptions of Their Emotional Experience and Parental Care: Preliminary Evidence of Positive Bias

Abstract: The tendency to perceive caregivers in highly positive terms and to perceive the self as strong and problem-free are two facets of the positive bias characteristic of a dismissing attachment classification in adulthood. However, this link has not yet been examined in children. We evaluated the association between dismissing attachment and positive bias in school-aged children's reports of their own emotional experience and their parental care, hypothesizing that: (1) compared to secure children, dismissing chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 51 publications
4
23
0
Order By: Relevance
“…This explanation is consistent with evidence that more avoidant adults are less attentive to emotional events when encoding the information (Farely, Garner, & Shaver, 2000). Borelli et al (2013) also proposed that avoidant children might prefer not to report their emotions, as a means not to notice their distress, which is consistent with evidence that avoidant children in middle childhood underreport their distress compared to their physiological response (Borelli et al, 2013; White et al, 2012). Additional studies with children are needed to determine whether the low reactivity to emotional events by more avoidant children reflect a lack of awareness of their emotions, or more active efforts to suppress their emotions.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This explanation is consistent with evidence that more avoidant adults are less attentive to emotional events when encoding the information (Farely, Garner, & Shaver, 2000). Borelli et al (2013) also proposed that avoidant children might prefer not to report their emotions, as a means not to notice their distress, which is consistent with evidence that avoidant children in middle childhood underreport their distress compared to their physiological response (Borelli et al, 2013; White et al, 2012). Additional studies with children are needed to determine whether the low reactivity to emotional events by more avoidant children reflect a lack of awareness of their emotions, or more active efforts to suppress their emotions.…”
Section: Discussionsupporting
confidence: 62%
“…Mikulincer, Shaver, & Pereg (2003) argued that suppression of emotional experiences decreases perceived threats that have been already encoded. Alternatively, rather than active suppression, Borelli and colleagues (Borelli, David, Crowley, Snavely, & Mayes, 2013) suggested that reports of low negative affect by avoidant children might indicate they are unaware of their emotions, or if aware, they might be unable to express their emotions. This explanation is consistent with evidence that more avoidant adults are less attentive to emotional events when encoding the information (Farely, Garner, & Shaver, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that dismissing children manifested a marked tendency to underreport their subjective distress, showing a greater discrepancy between subjective and physiological emotional response (White et al, 2012, 2013; Borelli et al, 2014), even in a non-relational context (Borelli et al, 2013). Despite their tendency toward a positive bias in perceiving their parents as more loving (Borelli et al, 2013), they showed a higher expectation of rejection by peers (White et al, 2012, 2013). These findings should be kept in mind when interpreting data from child-report measures of parental care and emotional experience.…”
Section: Resultsmentioning
confidence: 99%
“…These findings should be kept in mind when interpreting data from child-report measures of parental care and emotional experience. Furthermore, as Borelli et al (2013) suggested, future studies are needed to explore the development of the different dismissing strategies, namely those based on idealization and those based on the dismissal of the attachment figures as well as the dismissal of one's own attachment needs.…”
Section: Resultsmentioning
confidence: 99%
“…Agostini, et al, 2010; Barakat, Marmer, & Schwartz, 2010; Garralda, Rangel, Levin, Roberts, & Ukoumunne, 1999; Jenerette & Valrie, 2010) and has been adapted for use in children and adolescents whose age range from 8 to 18 (e.g. Barakat et al, 2010; Garralda et al, 1999; Gau & Chang, 2013; Borelli, David, Crowley, Snavely, & Mayes, 2013). In this study, children were asked to report only on the parent that was also participating in the study.…”
Section: Methodsmentioning
confidence: 99%